2009
DOI: 10.1371/journal.pone.0008245
|View full text |Cite
|
Sign up to set email alerts
|

IgG Autoantibody to Brain Beta Tubulin III Associated with Cytokine Cluster-II Discriminate Cerebral Malaria in Central India

Abstract: BackgroundThe main processes in the pathogenesis of cerebral malaria caused by Plasmodium falciparum involved sequestration of parasitized red blood cells and immunopathological responses. Among immune factors, IgG autoantibodies to brain antigens are increased in P. falciparum infected patients and correlate with disease severity in African children. Nevertheless, their role in the pathophysiology of cerebral malaria (CM) is not fully defined. We extended our analysis to an Indian population with genetic back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…PANAMA blot method was used to analyse autoantibody repertoire of sera samples from malaria and dengue patients and healthy participants (eight sera from each group), as described earlier . In brief, brain lysate proteins (200 μg/gel; Medley, Ozyme, France) were resolved on 10% SDS‐PAGE and transferred on nitrocellulose membrane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PANAMA blot method was used to analyse autoantibody repertoire of sera samples from malaria and dengue patients and healthy participants (eight sera from each group), as described earlier . In brief, brain lysate proteins (200 μg/gel; Medley, Ozyme, France) were resolved on 10% SDS‐PAGE and transferred on nitrocellulose membrane.…”
Section: Methodsmentioning
confidence: 99%
“…The bands developed in the anti‐IgG probed membranes were too faint for meaningful analysis and were not processed further. Membranes probed with anti‐IgM antibodies were dried and scanned by a high‐resolution scanner (600 DPI) using an 8‐bit linear grayscale as described . Subsequently, the proteins transferred to membranes were stained with colloidal gold (Protogold, British‐BioCell, GB), and the stained membranes scanned again.…”
Section: Methodsmentioning
confidence: 99%
“…An anti-P. falciparum HRP-2 IgM (MPFM-55A; Santa Cruz Biotechnology, France) was used as the capture antibody, an anti-P. falciparum HRP-2 IgG1 was used as a detection antibody (MPFG-55; Santa Cruz Biotechnology, France), and a horseradish peroxidase-coupled monoclonal anti-IgG1 antibody (SB77e; Abcam, France) was used as the secondary antibody for detection. A standard curve was added in duplicate to each plate, and it was obtained through serial dilutions of a serum sample from a previously described cohort with known parasitemia (18). Samples out of range of detection were more or less diluted.…”
mentioning
confidence: 99%
“…Despite these findings, the molecular mechanism of the IgG antibody production to the βIII during infection is still unknown. It seems that the IgG response against βIII found in the disease restrictively could be a new biomarker in the Indian population [35]. Some authors have found a correlation between disease stage and the presence of anticancer antibodies [6].…”
Section: Discussionmentioning
confidence: 98%